Hidden role of gut microbiome in mental health - A. Duarte; I. Simões; C. Cordeiro; P. Martins (European Psychiatry, 2022)
Introduction The recent literature indicates that the gut microbiota may affect brain functions through endocrine and metabolic pathways, antibody production and the enteric network while supporting its possible role in the onset and maintenance of several neuropsychiatric disorders, neurodevelopment and neurodegenerative disorders.